Antioxidant activity, acetylcholinesterase and tyrosinase inhibitory potential of Pulmonaria officinalis and Centarium umbellatum extracts - Neagu, Elena (Saudi J Biol Sci, 2018)
In this study several investigations and tests were performed to determine the antioxidant activity and the acetylcholinesterase and tyrosinase inhibitory potential of Pulmonaria officinalis and Centarium umbellatum aqueous extracts (10% mass) and ethanolic extracts (10% mass and 70% ethanol), respectively. Moreover, for each type of the prepared extracts of P. officinalis and of C. umbellatum the content in the biologically active compounds – polyphenols, flavones and proanthocyanidins was determined. The antioxidant activity was assessed using two methods, namely the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and reducing power assay. The analyzed plant extracts showed a high acetylcholinesterase and tyrosinase inhibitory activity in the range of 72.24–94.24% (at the highest used dose – 3 mg/mL), 66.96% and 94.03% (at 3 mg/mL), respectively correlated with a high DPPH radical inhibition – 70.29–84.9% (at 3 mg/mL). These medicinal plants could provide a potential natural source of bioactive compounds and could be beneficial to the human health, especially in the neurodegenerative disorders and as sources of natural antioxidants in food industry.